How Financial Distress Affect The Coping Strategy? Case Of Indonesian MSME’s During The Covid-19 Outbreak - Agus Triyani; Suhita Whini Setyahuni (Universitas Muhammadiyah Malang, 2023)
This research intends to examine the effect of financial distress, self-efficacy, and leadership skills on coping strategy in time of COVID-19 pandemic. This study focuses on the coping strategy implementation of MSMEs in Indonesia during economic downturn due to the pandemic. We examine 125 MSMEs in Indonesia as our respondents. We employ multinomial logistics regression technique to test the hypotheses. Our findings show that financial distress negatively affects the choice of coping strategy. On the other hand, self-efficacy and leadership skills have a positive impact on coping strategy. Financial distress, self-efficacy, and leadership skills are empirically proven as the determinant factors that influence the coping strategy selection process during the COVID-19 pandemic. This research uses a new perspective of financial distress scales and leadership skills aspects as a new insight in coping strategy decision making process. This study contributes to the development literature on coping strategy and its determinant factors during crisis conditions. practically, this research has implications to the development of coping strategy models and its influenced factors for business practitioners, especially on how to develop coping models during crisis condition.